2020
DOI: 10.1155/2020/8814092
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Optogenetics in Atrial Fibrillation: Current Challenges and Future Opportunities

Abstract: Although rarely life-threatening on short term, atrial fibrillation leads to increased mortality and decreased quality of life through its complications, including heart failure and stroke. Recent studies highlight the benefits of maintaining sinus rhythm. However, pharmacological long-term rhythm control strategies may be shadowed by associated proarrhythmic effects. At the same time, electrical cardioversion is limited to hospitals, while catheter ablation therapy, although effective, is invasive and is dedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 98 publications
(189 reference statements)
0
7
0
Order By: Relevance
“…The marketed NOACs include apixaban, dabigatran, edoxaban and rivaroxaban, which are available in a range of doses for a range of indications. However, the use of these anticoagulants with currently available dosage forms is associated with limited effectiveness and an increased risk of dose-related major bleeding [ 1 , 2 , 6 ]. Warfarin is recommended in clinical guidelines for the management of valvular AF and NVAF although long-term use requires frequent blood tests and involves the difficulty of achieving stable international normalized ratios, making therapy complex for physicians and patients.…”
Section: Pharmacotherapy and Limitations Of Current Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The marketed NOACs include apixaban, dabigatran, edoxaban and rivaroxaban, which are available in a range of doses for a range of indications. However, the use of these anticoagulants with currently available dosage forms is associated with limited effectiveness and an increased risk of dose-related major bleeding [ 1 , 2 , 6 ]. Warfarin is recommended in clinical guidelines for the management of valvular AF and NVAF although long-term use requires frequent blood tests and involves the difficulty of achieving stable international normalized ratios, making therapy complex for physicians and patients.…”
Section: Pharmacotherapy and Limitations Of Current Treatmentmentioning
confidence: 99%
“…Atrial fibrillation (AF) is the most prevalent cardiac arrhythmia worldwide and is associated with increased mortality and decreased quality of life through its complications such as heart failure and stroke [ 1 , 2 ]. It has been reported that more than 335 million people are suffering from AF globally [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Optogenetics, 4 , 5 , 6 , 7 , 8 , 9 that has become widespread in neuroscience, could in principle be relevant in the cardiac field too. 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 However, the approach still has a limited clinical applicability mainly because cell optical sensitivity is obtained by transduction with gene constructs carried by viral vectors.…”
Section: Introductionmentioning
confidence: 99%
“…Cardiac optogenetics has the potential to overcome limitations associated with electrical stimulation of heart that include high‐voltage shocks, low‐specificity, non‐synchronous depolarization, and myocardial tissue damage, and thus it may become established as an alternative method for electrical control of the heart (Entcheva & Kay, 2020; Williams & Entcheva, 2015). It offers a therapeutic potential in cardiac electrophysiology that includes restoration of pacemaking ability, cardiac resynchronization, mimicking and terminating cardiac arrhythmias, suppression and manipulation of rotors in cardiomyocyte monolayers, and elucidation of the function of both cardiomyocyte and non‐cardiomyocyte cellular subpopulations in the heart (Bruegmann et al., 2016; Floria et al., 2020; Nyns et al., 2017; O'shea et al., 2019; Wang et al., 2017).…”
Section: Introductionmentioning
confidence: 99%